Miracetyma kawa SP. NOV. (COPEPODA, POECILOSTOMATOIDA, ERGASILIDAE) DOS PEIXES DE ÁGUA DOCE DA AMAZÔNIA BRASILEIRA - Malta, Jose Celso de Oliveira (Acta Amazonica, 1993)
Miracetyma kawasp. nov. is proposed. The specimens were collected from the gill filaments of Rhaphiodum vulpinunAgassiz, 1829. The new species differs from the type-species, M. etimaruyain size and in the shape of the cephalothorax. Also, the cuticular extensions of the third antennal segment are limited to the internal and external distal margins and the rami of the legs have different shapes and armature.
Miracetyma kawa sp. nov. (Copepoda, Poecilostomatoida, Ergasilidae) from Freshwater Fishes of the Brazilian Amazon
Keywords: Copepoda; Poecilostomatoida; Ergasilidae; Parasites Of Fishes; Amazon; Copepoda; Poecilostomatoida; Ergasilidae; Parasitas De Peixes; Amazônia